The Influence Functional Status on The Quality Life Post Patients Stroke - Tiur Romatua Sitohang; Herlina Evi Yanti Manik (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Stroke is a functional brain disorder that occurs suddenly and is characterised by clinical symptoms both vocal and global which persist for a period exceeding 24 hours. These symptoms are caused by disorders affecting the blood circulation system. In patients who have suffered a stroke can result in difficulties for carrying out activities of daily living and in the development of motor skills. The research design was a correlational observational study with a cross-sectional approach. The study sample comprised 30 post-stroke patients. Inclusion criteria were patients post-stroke one year or more, seeking outpatient treatment at the Neurology Clinic from June to August 2024. Sampling was conducted using the purposive sampling technique. Spearman rho test for bivariat analysis is used to assess the impact of functional status on the quality of life of post-stroke patients. The research instrument was a questionnaire. The Functional Status Questionnaire employs the Barthel Index scale. The respondent indicated that they were fully independent. The quality of life questionnaire employs the Short Form Stroke-Specific Quality of Life Scale (SSQOL). P-value for the spearman correlation test is 0.046 (<0.05) indicates that there is a statistically significant influence between functional status and the patient's quality of life. The correlation coefficient value is r=0.368, indicating that the influence between functional status and quality of life is moderate to strong. These positive results indicate that as an individual's functional status improves, so does their quality of life one year after stroke. Consequently, the functional status of these patients can be improved through stroke rehabilitation, which is designed to enhance quality of life. Keywords: Functional Status, Stroke, Quality of Life